Systemic Inflammatory Immune Index (SII) Predicts Disease Activity in Systemic Lupus Erythematosus (SLE) Patients: A Cross-Sectional Study - Susanto, Edi; Yuniza; Legiran; Nova Kurniati; Eddy Mart Salim (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by widespread inflammation and diverse clinical manifestations. The systemic inflammatory immune index (SII), calculated as platelet count * neutrophil count/lymphocyte count, has emerged as a potential marker of systemic inflammation in various conditions. This study aimed to investigate the relationship between SII and disease activity in SLE patients. Methods: We conducted a cross-sectional study involving 60 SLE patients diagnosed according to the 2019 EULAR/ACR classification criteria. Demographic and clinical data were collected, and disease activity was assessed using the Mexican Systemic Lupus Erythematosus Disease Activity Index (MEX-SLEDAI). Blood samples were analyzed to determine SII values. Statistical analysis included Spearman's correlation to assess the relationship between SII and MEX-SLEDAI scores. Results: The study population predominantly consisted of women (98.3%), with a median age of 29 years. A strong positive correlation was observed between SII and MEX-SLEDAI scores (r = 0.931, p < 0.001). Patients with higher SII values exhibited significantly greater disease activity. Conclusion: Our findings suggest that SII is a promising predictor of disease activity in SLE patients. This readily available index may aid clinicians in assessing disease severity and tailoring treatment strategies. Further research is warranted to validate these findings and explore the utility of SII in monitoring disease progression and treatment response.